Cellular senescence: Molecular mechanisms and pathogenicity. Issue 12 (5th August 2018) - Wei, Wenqiang; Ji, Shaoping
Abstract : Cellular senescence is the arrest of normal cell division. Oncogenic genes and oxidative stress, which cause genomic DNA damage and generation of reactive oxygen species, lead to cellular senescence. The senescence‐associated secretory phenotype is a distinct feature of senescence. Senescence is normally involved in the embryonic development. Senescent cells can communicate with immune cells to invoke an immune response. Senescence emerges during the aging process in several tissues and organs. In fact, increasing evidence shows that cellular senescence is implicated in aging‐related diseases, such as nonalcoholic fatty liver disease, obesity and diabetes, pulmonary hypertension, and tumorigenesis. Cellular senescence can also be induced by microbial infection. During cellular senescence, several signaling pathways, including those of p53, nuclear factor‐κB (NF‐κB), mammalian target of rapamycin, and transforming growth factor‐beta, play important roles. Accumulation of senescent cells can trigger chronic inflammation, which may contribute to the pathological changes in the elderly. Given the variety of deleterious effects caused by cellular senescence in humans, strategies have been proposed to control senescence. In this review, we will focus on recent studies to provide a brief introduction to cellular senescence, including associated signaling pathways and pathology. Abstract : Cellular senescence is linked to many human diseases. In this review, we will focus on recent studies to provide a brief overview of cellular senescence, including associated signaling pathways and pathology.